Students’ Perception towards E-Learning During The Covid-19 Pandemic at The Eleventh Grade of SMA Negeri 3 Palopo - Indah Maharani; Nasmilah Nasmilah; Abidin Pammu (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The popularity of online learning in education became pervasive immediately during the outbreak of COVID-19. There are so many obstacles that lecturers and students may face while doing online learning throughout some applications, especially in areas that experience difficulties or obstacles while using the online system. This research aimed to figure out the students’ perception towards e-learning/online learning during the covid-19 pandemic at the eleventh grade of SMA Negeri 3 Palopo. The method that the researcher used in this research was the descriptive qualitative method and through the online questionnaire, the researcher administered open-ended questionnaire to the eleventh grade of the students in SMA Negeri 3 Palopo. The data was analyzed using descriptive qualitative analysis. The result of this research indicates that the students had a negative perception towards e-learning during the covid-19 pandemic because the online learning was not effective enough. Some obstacles/problem were faced during the online learning was the unstable network, hard to understand the material, lack of internet quota, and lack of motivation.